RITUAL OF THE MARTUTUAEK CEREMONY IN MAINTAINING THE IDENTITY OF THE PARMALIM COMMUNITY IN MEDAN CITY - Ari Suhada; Muhammad Jailani (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Martutu Aek is one of the important rituals in Ugamo Malim which functions as a purification ceremony and naming of newborn babies, this ritual is still maintained by the Parmalim people in Medan City despite facing changes due to urban life. This study aims to describe the implementation of Martutu Aek, analyze its symbolic and theological meaning, and examine its role in maintaining the cultural and religious identity of the Parmalim community in the city of Medan. The research uses a qualitative approach with a descriptive method. Data were obtained through observation, interviews with religious leaders and Parmalim congregations, as well as literature studies, then analyzed through data reduction, data presentation, and conclusion drawn. The results of the study show that Martutu Aek contains symbolic meaning through the use of water, itak gur-gur, rimbang leaves, and weed leaves as symbols of purity, welfare, hope, and steadfastness of life. Theologically, this ritual is an expression of gratitude to Debata Mulajadi Na Bolon and a commitment to guide children according to the teachings of Ugamo Malim. In the midst of the multicultural community of Medan City, Martutu Aek continues to play a role as a medium for preserving the cultural and religious identity of the Parmalim community through the inheritance of values, strengthening community solidarity, and preserving ancestral traditions.